Digital nativity of university teachers in China: factor structure and measurement invariance of the Digital Native Assessment Scale (DNAS). Issue 3 (3rd April 2021) - Huang, Fang; Teo, Timothy; He, Jinbo
ABSTRACT: This study examined the digital nativity of university teachers in China and tested the factor structure and measurement invariance from exploratory structural equation modelling analyses of the Digital Native Assessment Scale (DNAS) developed by Teo [(2013). An initial development and validation of a digital natives assessment scale (DNAS). Computers & Education, 67, 51–57]. Data were collected from 502 university teachers from 11 Chinese universities. The results indicate that Chinese university teachers demonstrate "digital native" characteristics. The results also support the measurement invariance of the DNAS across age, teaching experience, years of technology use, and years of teaching with technology. This study is the first in the digital native literature to examine the digital nativity of teacher cohorts using the DNAS. It addresses the issue of age when characterising digital natives and enriches our understanding of digital natives by empirically proving the validity of the DNAS in measuring teachers' digital nativity in China. This study also has implications for policy makers who develop technology-related education policies and design continuing professional development training.